Linear multi-degree-of-freedom low-frequency piezoelectric vibration energy harvester. (25th September 2016) - Wang, Yanfen; Luo, Cuixian; Li, Pengwei
ABSTRACT: A linear multi-degree-of-freedom piezoelectric energy harvester has been designed in this paper. The proposed energy harvester was comprised by multi-order transmission beams and traditional single cantilever beam. As the transmission beam order increases, the resonant frequencies of this kind of harvester could be tuned and reduced efficiently. The first three modes of the three-degree-of-freedom harvester occur within the range of 0-100 Hz, reaching a fair agreement with the simulation. The operating bandwidth expands to 15 Hz, 375% of the conventional piezoelectric cantilever beam, which made this designed harvester a good candidate for energy scavenging in multi-sources and wide-frequency vibration environment.